RETURNS AND VOLATILITY SPILLOVER BETWEEN ASIAN EQUITY MARKETS: A WAVELET APPROACH - S Kumar, Anoop; Kamaiah, B (Economic Annals, 2017)
We analyse return and volatility spillover across select Asian equity markets using wavelet multiple correlation and cross-correlation. For the purpose of analysis, daily return data is taken from equity markets, viz. Bombay Stock Exchange SENSEX, Tokyo Stock Exchange NIKKEI 225, Hong Kong Shanghai Index (HSI), Amman Equity Index, Korea Composite Stock Price Index (KOSPI), and Singapore Strait Time Index (STI), from 03/01/2000 to 31/12/2013. The results show that the Asian markets are co-integrated in the long run. Further, it is found that a significant part of each market’s volatility pattern at intraweek scale can be largely explained by own shocks, but in the long run the volatility dynamics of the market changes as the extent of the spillover increases. From the wavelet multiple cross-correlation values, two developed markets, the STI and the HSI, are identified as potential leaders or followers among the group. From the analysis it is found that the volatility spillover across the studied markets is relatively low at the high frequency, implying that there is possibility of diversification at a daily to intraweek scale. The discrepancies between the markets vanish in the long run; hence a long-term diversification strategy is best avoided.